A Monte Carlo approach to simulate dendritic microstructures during binary alloy solidification. (15th October 2020) - Pal, Prabhakar; Abhishek, G S; Karagadde, Shyamprasad
Abstract: A Monte Carlo (MC) approach to model the evolution of microstructures during the binary alloy solidification process has been presented. The evolution of these microstructures is comprehensively modelled by ensuring a local minimization of free energy taking into account the contributions of the free energy change during phase transformation, solid-liquid interfacial energy, interfacial energy anisotropy and grain boundary energy, which are some of the ignored aspects of the existing MC models. Further, the effect of imposed orientation is also represented in this model. The proposed method is able to simulate the preferential growth of cubic structures in ⟨100⟩ direction, growth of large number of grains and competition among them, and also incorporates the grain boundary energetics. The model is applied to simulate the growth of free and constrained dendrites, the transition from stable to cellular and dendritic growth under different growth conditions. Growth of multiple grains, the competition during columnar growth, columnar to equiaxed transition by seeding the undercooled melt with solid phase and the impingement of equiaxed grains has also been simulated using this model.